Policy and Management of Covid-19 by Village Government - Ragilia Putri Wandansari; Harun Harun; Natangsa Surbakti; Moh Indra Bangsawan; Dewi Kusuma Diarti; Arief Budiono (Health Notions, 2021)
The 1945 Constitution of the Republic of Indonesia Article 28 H states that every person has the right to live in physical and mental prosperity, to have a place to live, and to have a good and healthy living environment and the right to obtain health services. This study aims to 1). Describe the policy for handling and overcoming the pandemic - Covid-19; 2). Describe the village government-based policies for handling and overcoming the Covid-19 pandemic. This research was a normative legal research conducted by examining library materials or secondary data. The approach used was a statutory approach and a conceptual approach. The type of study in this research was more descriptive in nature, because it intends to clearly describe various things related to the object under study. The policy for handling and overcoming the Covid-19 pandemic is marked by the formation of a Task Force for the Acceleration of Handling Covid-19 through Presidential Decree Number 7 of 2020. However, until now the number of positive cases of Covid-19 continues to increase to 1,505,800 people positive for Covid-19 cases in Indonesia as of March 30, 2021. In fact, the government has issued a new policy namely the Enforcement of Community Activity Restrictions (PPKM) and intensified the Covid-19 vaccination program. Therefore, the government needs to optimize the village government-based Covid-19 handling policy that better understands the environment by empowering all stakeholders in an effort to reduce the growth rate of Covid-19. Keywords: Covid-19 prevention policy; village government